Pengembangan Math Domino Cards Untuk Meningkatkan Pemahaman Konsep Bilangan Bulat Siswa Kelas VII SMP/MTs - Siti Aisah; Mukarromatul Isnaini; Sinar Marhamah; Ahmad Rasidi; Sri Supiyati (FKIP Universitas Mataram, 2026)
This study focused on developing and testing the feasibility of Math Domino Cards as a learning medium for integer material by reviewing its validity, practicality, and effectiveness in improving the conceptual understanding of SMP/MTs. The method used was Research and Development (R&D) with a 4D model that included the stages of define, design, develop, and disseminate. The study involved 34 students from class VII MTs Mu’allimin NWDI Pancor as test subjects. The instruments used included material and media expert assessment sheets, practicality questionnaires for teachers and students, and concept comprehension tests conducted through pre-tests and post-tests. Data analysis was performed using quantitative descriptive statistics, N-Gain calculations, and paired t-tests. The results of the analysis showed that the Math Domino Cards media was in the valid category with a percentage of material expert and media expert assessments of 75% each. The practicality of the media was classified as good based on the responses of 77% of teachers and 71.98% of students. Effectiveness testing showed an increase in understanding of integer concepts with an N-Gain value of 0.3008 in the moderate category, as well as a significant difference between the pretest and post-test results based on the paired t-test. These findings indicate that the application of integer-based domino card games through the 4D model is feasible and has the potential to improve the quality of students' understanding of mathematical concepts.